Dynamic release and perception of key odorants in grilled eel during chewing. (1st June 2022) - Huang, Xu-Hui; Luo, Yong; Zhu, Xiao-Hui; Ayed, Charfedinne; Fu, Bao-Shang; Dong, Xiu-Ping; Fisk, Ian; Qin, Lei
Highlights: Release and perception of odorants in grilled eel during chewing were monitored. External standard method can be used to quantify key odorants during chewing. Two cycles/s was a great chewing frequency for eating. The aroma perception during eating grilled eel was divided into three stages. Abstract: The release mechanism of odorants in the oral cavity during consumption directly affects sensory attributes, consumers' preferences, and ultimately purchase intent. Targets was set to monitor in real-time the key odorants released from grilled eel during mastication via an atmospheric pressure chemical ionization mass spectrometry (APCI-MS) connected with a nose interface. The release and perception of odorants during mastication were divided into three distinct phases. Dimethyl sulfide was the main odorant in the first stage. The release and perception of fishy aromas were predominant in the middle and last stages of mastication contributed by trimethylamine, 1-penten-3-ol, and 2-methyl-1-butanol. Chewing behavior experiments suggested that extending the chewing period to >20 s and having a chewing frequency of 2 cycles/s could enhance the aroma delivery of grilled eel and optimize the consumer experience. Consequently, the results explained the relationship between aroma release and the optimal chewing behavior for grilled eel consumption.